2022
DOI: 10.1155/2022/3938652
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Molecular Characterization Revealed the Prognosis Efficiency of Histone Acetylation in Pan-Digestive Cancers

Abstract: The imbalance between acetylation and deacetylation of histone proteins, important for epigenetic modifications, is closely associated with various diseases, including cancer. However, knowledge regarding the modification of histones across the different types of digestive cancers is still lacking. The purpose of this research was to analyze the role of histone acetylation and deacetylation in pan-digestive cancers. We systematically characterized the molecular alterations and clinical relevance of 13 histone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…Interestingly, Kaplan-Meier curves available at the Human Protein Atlas (proteinatlas.org) (40) demonstrate that cancers in which high HDAC10 expression is associated with poor prognosis include those that are associated with TMEs enriched in excretory products, including renal cancer and colon adenocarcinoma. A recent analysis of TCGA data reported HDAC10 copy number gains as a risk factor for colorectal and pancreatic cancers (41). A study of colon cancer patients in China reported constitutively elevated expression of HDAC10 protein in tumor tissues compared to paired adjacent tissue in the majority of patients J o u r n a l P r e -p r o o f (9), with the greatest difference observed in cytoplasmic HDAC10.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Kaplan-Meier curves available at the Human Protein Atlas (proteinatlas.org) (40) demonstrate that cancers in which high HDAC10 expression is associated with poor prognosis include those that are associated with TMEs enriched in excretory products, including renal cancer and colon adenocarcinoma. A recent analysis of TCGA data reported HDAC10 copy number gains as a risk factor for colorectal and pancreatic cancers (41). A study of colon cancer patients in China reported constitutively elevated expression of HDAC10 protein in tumor tissues compared to paired adjacent tissue in the majority of patients J o u r n a l P r e -p r o o f (9), with the greatest difference observed in cytoplasmic HDAC10.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of Plk1 phosphorylation and its downstream target HBO1 reverse the onset of resistance. However, abnormal expressions of several other histone‐modifying enzymes were also identified 259 . The high transcriptional levels of HDAC7 and HDAC2 are involved in the progression of pancreatic cancer 260 .…”
Section: Abnormal Expression Of Histone‐modifying Enzymes and Human C...mentioning
confidence: 99%
“…The obtained results revealed that low expression of H3K18Ac and H3K27triMe was associated with better prognosis in patients with ESCC, especially in early-stage patients ( Tzao et al, 2009 ). In addition, Zhang et al (2022) investigated five digestive cancers, including esophageal, gastric, hepatocellular, pancreatic and colorectal cancers, by systematically examining 13 HAT and 18 HDAC genes. As a result, histone acetylation was found to be a key regulatory molecule in digestive cancer.…”
Section: Epigenetics In the Prognosis Of Esophageal Cancermentioning
confidence: 99%